The Mind Is Not a Kludge. - Perlovsky, Leonid (Skeptic, 2010)
The article offers analysis and argumentation on the mechanisms and unique purposes of brain relative to the claims that the mind is a kludge. According to Marvin Minsky, the function of the brain is based on the thousands of principles and a collection of kludges. Furthermore, Elizabeth Spelke, Professor of Psychology at Harvard University, stressed that humans are capable neither general-purpose learning system nor with myriad special-purpose systems.